Partnered decision support: Parental perspectives of completing a pre‐visit pediatric asthma questionnaire via the patient portal. Issue 1 (26th October 2021) - Ross, Mindy K.; Friedman, Sarah; Radparvar, Ilana; Ryan, Gery
Abstract : Background: Collection of patient‐reported data has been demonstrated to improve asthma outcomes. One method to collect information is through the electronic patient portal. In practice, patient portal use in pediatrics and, specifically for asthma management, has had low uptake. Objective: To understand parental/caregiver experience of pediatric asthma care management, and perceptions of the use of patient portal questionnaires before the clinic visit. Methods: We conducted semi‐structured interviews with caregivers of children 5–11 years old with asthma in the University of California, Los Angeles (UCLA) Health System. We included patient portal "users" ( n = 20) and "non‐users" ( n = 5). Interview questions were developed based on clinic visit workflow with a focus on perceived usefulness and ease of use to complete pediatric asthma questionnaires in the patient portal before the visit. Interviews were audio‐recorded, transcribed, and codes were generated from themes using constant comparative analysis. Results: We identified eight themes related to caregiver‐physician communication, perception of portal questionnaires, facilitators, and barriers to portal questionnaire use. A salient finding was that caregivers considered the portal questionnaire as a tool to be integrated into the visit to facilitate a conversation about their child's asthma. Caregiver portal‐based questionnaire use was more likely if the ongoing data entered was accessible to caregivers to track and update, and if caregivers were reassured the clinicians would use questionnaire responses during the visit. Conclusion: Caregivers of children with asthma are more likely to complete a patient portal intake questionnaire before the visit if they trust their responses will be used during the visit to inform care.